Building a Strategic Framework for Comparative Effectiveness Research in Complementary and Integrative Medicine. (26th December 2012) - Witt, Claudia M.; Chesney, Margaret; Gliklich, Richard; Green, Lawrence; Lewith, George; Luce, Bryan; McCaffrey, Anne; Rafferty Withers, Shelly; Sox, Harold C.; Tunis, Sean; Berman, Brian M.
Abstract : The increasing burden of chronic diseases presents not only challenges to the knowledge and expertise of the professional medical community, but also highlights the need to improve the quality and relevance of clinical research in this domain. Many patients now turn to complementary and integrative medicine (CIM) to treat their chronic illnesses; however, there is very little evidence to guide their decision-making in usual care. The following research recommendations were derived from a CIM Stakeholder Symposium on Comparative Effectiveness Research (CER): (1) CER studies should be made a priority in this field; (2) stakeholders should be engaged at every stage of the research; (3) CER study designs should highlight effectiveness over efficacy; (4) research questions should be well defined to enable the selection of an appropriate CER study design; (5) the CIM community should cultivate widely shared understandings, discourse, tools, and technologies to support the use and validity of CER methods; (6) Effectiveness Guidance Documents on methodological standards should be developed to shape future CER studies. CER is an emerging field and its development and impact must be reflected in future research strategies within CIM. This stakeholder symposium was a first step in providing systematic guidance for future CER in this field.